Home schooling through online teaching in the era of COVID-19: Exploring the role of home-related factors that deepen educational inequalities across European societies. (July 2021) - Dimopoulos, Kostas; Koutsampelas, Christos; Tsatsaroni, Anna
The COVID-19 pandemic has forced governments worldwide to produce solutions to the abruptly interrupted work in education. School systems appear to have responded rapidly, creating home schooling and online educational environments, where teachers and students would interact with safety. In this paper, we attempt a synthesis of Sen's capability approach, Bourdieu's theory of capital and Bernstein's framework in order to theorize the relationships between home and school conditions and practices, and to analyse the data of the 2nd Survey of Schools: ICT in Education (a survey conducted in 2019 on behalf of the European Commission collecting data regarding digitalization in education and digital technologies in learning in the European Union). The survey is complemented by a second set of indicators provided by Eurostat to further investigate the availability and functionality of household space per family in selected European countries. We find significant differences in important social and environmental conversion factors, likely limiting children's capability to benefit from digital schooling. The most important differences are found in regard to parents' familiarity with information and communications technology use, while inequalities in environmental factors, such as overcrowded housing, are also existent. Overall, there are large inequalities within and between countries in Europe, which need to be addressed by policymakers.